Design Concept of a Motorcycle Secondary Electronic Lock - Madon, Rais Hanizam; Fawzi, Mas; Sarwani, Muhamad Khairul Ilman; Amat Azman, Putera Mohamad Adam; Abdullah, Ahmad Fauzan; Abdullah, Mohamad Ashik (International Journal of Integrated Engineering, 2021)
Design process of a motorcycle secondary electronic lock system is reported in this paper. The design of a smart lock was established based on an available conventional lock in the market. The process began with design generation to gather related idea and design concept. The design then was subjected to concept evaluation through a design matrix to determine the best option. In addition, selection of internal component and mechanism were evaluated through a morphological chart. The design and component were selected based on the highest score in term of functionality, fabrication, safety and marketability. The chosen design was then converted to a 3D model using computer aid design (CAD) and a simulation strength test was applied to the model by using a commercial software. The simulation using common hacking tool used by theft was successfully conducted and showing positive results on its robustness.